The effect of online learning on student satisfaction in nursing education during the COVID-19 pandemic - Hikmatul Qowi, Nurul; Suratmi, Suratmi; Faridah, Virgianti Nur; Lestari, Trijati Puspita; Pramestirini, Rizky Asta; Karsim, Karsim; Pamungkas, Nanda Rifqi Tri (Jurnal Ners, 2022)
Introduction: Online learning is a global trend in higher education in the era of the COVID-19 pandemic. Online learning becomes one of the approaches available to most students and educators, as opposed to face-to-face learning. The aim of this research is to find out the correlation of online learning and satisfaction among nursing students during the COVID-19 pandemic. Methods: This study was a cross-sectional approach involving 177 second-year nursing students randomly selected resulting in 121 students. Students filled out an online learning questionnaire consisting of 14 items and a satisfaction questionnaire consisting of 21 items from Google Forms. Data were analysed using logistic regression with level of significance (p=0.000). Results: The online learning indicator that had the highest average value was relevance (3.12), while the highest average value of student satisfaction indicator was content (3.05). Logistic regression showed that the online learning indicator that greatly affected student satisfaction was attractiveness. Fair attractiveness for online learning increased satisfaction by 7.516 times compared to poor attractiveness (p = 0.000) and good attractiveness for online learning increased satisfaction by 55.538 times compared to poor attractiveness (p = 0.000). Conclusions: Student satisfaction depends heavily on student attractiveness to the online learning process. Lecturers can increase the attractiveness of students toward online learning, whether through the utilized media, learning methods, or the technology of delivering lecture materials.